The Use of Ecological Momentary Assessments to Measure Perceived Stress in People With Aphasia: A Feasibility Study. - Jewell, Courtney C.; Krok-Schoen, Jessica L.; Harnish, Stacy M. (Journal of Speech, Language & Hearing Research, 2025)
Purpose: People with aphasia (PWAs) report higher levels of stress than people without aphasia. Stress can have adverse effects on physical and mental health and may lead to harmful changes in the body's neurological functioning. Moreover, the perception of stress is a dynamic construct, and considerable fluctuations in symptom severity occur. Ecological momentary assessments (EMAs), or data sampling in an individual's real environment, have been increasingly used in health care research, but their application to PWAs has yet to be explored. This study aimed to assess the feasibility and compliance of interval-contingent EMAs to measure perceived stress in the real world for PWAs. Method: Twenty-five participants from a larger parent study participated in the EMA protocol. Participants were sent text messages with a link to answer five prompts regarding stress severity once a day for 10 consecutive days. Results: Out of the 29 participants screened, 25 were successfully enrolled in the EMA portion of the study, achieving a feasibility rate of 86%. Compliance was 93.2%, which exceeded the compliance goal of ≥ 80%. The mean baseline stress score was 16.56 (range: 2.00--37.00), and the mean general stress score from EMA reports was 1.98 (range: 1.00--3.25). Mean general stress ratings from the EMA reports showed a moderate, positive relationship with baseline stress, r = .56, S = 1131.5, p = .003. Discussion: This study found evidence to support the feasibility and compliance of interval-contingent EMAs for PWAs. Current research examining chronic stress and the development of therapeutic interventions can be expanded upon using EMAs. Supplemental Material: https://doi.org/10.23641/asha.29885360